Inventarisasi Lichen (Lumut Kerak) Di Kecamatan Banjarsari Di Kota Surakarta Provinsi Jawa Tengah - Aprihastuti, Mega; , Efri Roziaty, S. Si., M. Si (2018)
The lichen spesies found in Banjarsari sub-district in SurakartaCity Central Java Province have not been identified. The purpose of this to know the type of lichen that exist along the road n District Banjarsari in Surakarta City Central Java Province. Data collection method used s survey method conducted in two research stasions. Data of research result analysed by qualitative exploration are presented in table and picture. The results of the study were 5 spesies, among others Dirinaria picta, Parmelia sulcata, Flavoparmelia sp., Dirinaria applamata, and Lepraria incana, and included in 3 families that is Family Stereocaulaceae, Family Parmeliaceae and Family Caliciaceae. The observation made on both stations show that the percentage of lichen on the bark tree substrate show different values. Each lichen species in each station has a percentage value below 50%. Monitoring amountof vechicles passing trhough Banjarsari Sub-district in Surakarta City Central Java Provinve is densely packed as it show the number of ± 96,576 vehicles every day. Keywords : Banjarsari District, Inventory, Vehicle Monitoring.